Analiz tematiki doktorskikh i kandidatskikh dissertatsii ... po spetsial'nosti ... teoriya i metodika fizicheskogo vospitaniya, sportivnoi trenirovki utverzhdennykh ... v Rossii v 1995 - 1996 - Zaguzov, N. I. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
Analysis of dissertations in the field of physical culture, health education and sports in Russia 1995 - 1996. It is shown in what fields the works were written, which subjects the authors dealt with. And there is a list of the works. The dissertations were written in the following topics: - physical culture - 5 (from this 1 in health education), - top level sports - 11, - top level physical education - 2, - control of physical culture and sports - 1, - biomechanics - 2.